Complex Spinal Dysraphism Complicated by Intramedullary Dermoid - Sedain, Gopal; Sharma, Mohan Raj; Shilpakar, Sushil Krishna (Journal of Nepal Paediatric Society, 2016)
Spinal dysraphism presents in myriad ways. Meningomyeloceles presenting with Split cord malformations are termed as complex dysraphisms. We encountered a child with myelomeningocele and a split cord with intramedullary lesion making it a more complex dysraphism. J Nepal Paediatr Soc 2015;35(3):277-279